Keabsahan Jual Beli Di Bawah Tangan Tanah Transmigrasi Di Kabupaten Mamuju Tengah - Muh. Galil Gibran; Rofiq Laksamana; Dian Aries Mujiburohman (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2022)
The government provides land for the implementation of transmigration. The land is granted with the status of property rights on the condition that it cannot be traded for 20 (twenty) years. However, many transmigrants do not feel at home and choose to return to their original areas, by selling the transmigration land to other parties before 20 years. The sale and purchase of transmigration land is carried out under the hands without a deed from PPAT. So the problem studied is the legality of buying and selling under the hands and how to resolve it to register land at the Land Office if there is no PPAT deed, because the seller's whereabouts are unknown. This study uses empirical normative legal research methods with primary data sources through interviews. The results of the study show that buying and selling under the hands according to customary law is legal as long as it meets the requirements, namely clear and cash, but buying and selling under the hands without a deed of sale and purchase made by PPAT cannot be registered at the Land Office.